High-voltage electrolyte matched with sodium vanadium fluorophosphate positive material and sodium ion battery

CN116598592BActive Publication Date: 2026-10-20SHANDONG HIRONG POWER SUPPLY MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310520777.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2026-10-20
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

[0004]然而,钠离子能量密度低,应用范围受限,相关技术中一般通过提高电池的工作电压来提高钠离子电池的能量密度,但是常规电解液在高电压下的副反应会加剧,容易导致电池寿命降低,从而影响整个电池的循环性能和安全性能

Benefits of technology

[0023](1)本发明提出的匹配氟磷酸钒钠正极材料的钠离子电池高压电解液及钠离子电池采用高浓钠盐电解液匹配氟磷酸钒钠正极材料,在高压下,界面处溶剂的分解减少,自由溶剂的数量减少,从而扩展了电化学窗口,大大提高了氟磷酸钒钠正极材料的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116598592B_ABST
    Figure CN116598592B_ABST
Patent Text Reader

Abstract

The application provides a high-voltage electrolyte matched with a sodium-ion battery positive electrode material of sodium vanadium fluorophosphate, which comprises a sodium salt and a nonaqueous organic solvent, the sodium salt is one or more of sodium hexafluorophosphate, sodium bis(oxalato)borate, sodium bis(fluorooxalato)borate and sodium bis(fluorosulfonyl)imide, and the concentration of the sodium salt is 3.0-4.0 mol / L. Through the technical scheme, the high-concentration sodium salt electrolyte is matched with the sodium vanadium fluorophosphate positive electrode material, so that the sodium vanadium fluorophosphate positive electrode material maintains good stability under high temperature and high pressure, the generation of HF is inhibited, the occurrence of the side reaction between the electrolyte and the electrode under high pressure is reduced, and the sodium vanadium fluorophosphate positive electrode material exhibits good electrochemical performance under high pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, and more specifically, to a high-voltage electrolyte for sodium-ion batteries that is matched with sodium vanadium fluorophosphate cathode material, and a sodium-ion battery. Background Technology

[0002] Lithium-ion batteries are currently widely used in smartphones and electric vehicles. However, the reserves of lithium and cobalt, the raw materials for producing lithium batteries, are limited, and recycling requires high standards. To help achieve my country's dual-carbon goals, researchers have been working to develop sodium-based batteries, which use cheaper and more readily available materials.

[0003] Sodium-ion batteries work on the same principle as lithium-ion batteries, have similar manufacturing processes, and are characterized by abundant resources, low cost, and good safety performance. Sodium, the main component of sodium-based batteries, can be extracted from seawater, making it a plentiful and environmentally friendly resource.

[0004] However, sodium ions have low energy density, which limits their application range. In related technologies, the energy density of sodium ion batteries is generally increased by raising the battery's operating voltage. However, the side reactions of conventional electrolytes are aggravated at high voltages, which can easily lead to a reduction in battery life and thus affect the overall cycle performance and safety performance of the battery. Summary of the Invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.

[0006] Therefore, one objective of this invention is to provide a high-voltage electrolyte for sodium-ion batteries and a sodium-ion battery that is matched with sodium vanadium fluorophosphate cathode material. By using a high-concentration sodium salt electrolyte to match the sodium vanadium fluorophosphate cathode material, the sodium vanadium fluorophosphate cathode material maintains good stability under high temperature and high pressure, suppresses the generation of HF, reduces the occurrence of side reactions between the electrolyte and the electrode under high pressure, and enables the sodium vanadium fluorophosphate cathode material to exhibit good electrochemical performance under high pressure.

[0007] To achieve the above objectives, the first aspect of the present invention provides a high-voltage electrolyte for sodium-ion batteries that is matched with sodium vanadium fluorophosphate cathode material, comprising a sodium salt and a non-aqueous organic solvent, wherein the sodium salt is one or more of sodium hexafluorophosphate, sodium bis(oxalate-borate), sodium difluorooxalate-borate, and sodium difluorosulfonamide, and the concentration of the sodium salt is 3.0 mol / L to 4.0 mol / L.

[0008] In this technical solution, a high-concentration sodium salt electrolyte of 3.0 mol / L to 4.0 mol / L is used to match the sodium vanadium fluorophosphate cathode material. This not only improves the high-voltage resistance of the battery, but also forms a more stable CEI film, avoiding the passivation capability of common non-high-voltage solvent differences. The high-concentration sodium salt electrolyte can enhance the interaction between cations and solvent molecules, reduce the reactivity of the solvent, reduce the occurrence of side reactions, inhibit the generation of HF, and improve the cycle performance of the sodium vanadium fluorophosphate cathode material under high voltage. This breaks the technical bias in the prior art where excessively high sodium salt concentration leads to increased viscosity, difficulty in fully dissolving sodium salt, and easy rapid deterioration of battery performance. Usually, the sodium salt concentration needs to be designed to not exceed 2 mol / L.

[0009] In the above technical solution, preferably, the non-aqueous organic solvent is any one or more of fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, adiponitrile, succinic acid, ethyl acetate, and sulfolane.

[0010] In this technical solution, the non-aqueous organic solvent has high polarity, which further ensures that even sodium salts with excessively high concentrations can be fully dissolved.

[0011] In any of the above technical solutions, preferably, the concentration of the sodium salt is 3.5 mol / L.

[0012] In this technical solution, the concentration of sodium salt is controlled at 3.5 mol / L. Under high pressure, the amount of free solvent is reduced due to the decomposition of solvent at the interface, which expands the electrochemical window and greatly improves the cycle stability of sodium vanadium fluorophosphate cathode material. After 80 cycles at high temperature, the capacity retention rate of the high-concentration sodium salt electrolyte is 96.66%, which is much higher than that of conventional electrolytes.

[0013] In any of the above technical solutions, preferably, the sodium salt is sodium hexafluorophosphate.

[0014] In this technical solution, sodium hexafluorophosphate is used as the sodium salt, which further ensures sufficient solubility at higher concentrations.

[0015] In any of the above technical solutions, preferably, the non-aqueous organic solvent is a mixture of fluoroethylene carbonate and methyl ethyl carbonate in a volume ratio of 3:7.

[0016] In this technical solution, a mixture of fluoroethylene carbonate and methyl ethyl carbonate is used as a solvent, and the volume ratio is controlled, which can further improve the stability of the electrolyte and the solubility of sodium salt.

[0017] Preferably, the electrolyte is prepared in a glove box filled with argon gas and containing less than 1 ppm of water and less than 1 ppm of oxygen; the water content of the non-aqueous organic solvent is less than 1 ppm; and the water content of the sodium salt is less than 1 ppm.

[0018] The second aspect of the present invention provides a sodium-ion battery, which uses the high-voltage electrolyte of the sodium-ion battery described in any of the above technical solutions, and the positive electrode material is sodium vanadium fluorophosphate.

[0019] In this technical solution, a high-concentration sodium salt electrolyte is used to match the sodium vanadium fluorophosphate cathode material. This increases the interaction between solvent molecules and cations and anions, reduces the amount of free solvent in the electrolyte system, and weakens the dissolution effect of free solvent on the SEI, thereby stabilizing the battery interface. This high-concentration sodium salt forms a new electrolyte with a special three-dimensional structure. The reduction of free solvent molecules leads to the formation of obvious ionic morphologies and produces a solvated structure containing a large number of contact ion pairs (CIP) and ion aggregates (AGG). Under this electrolyte structure, significant advantages such as high rate performance, high cycle stability, high energy density, and high safety can be achieved.

[0020] In the above technical solution, preferably, the mass ratio of positive electrode material, conductive agent and binder in the positive electrode sheet is (7-9):(0.5-2):(0.5-1).

[0021] In the above technical solution, preferably, the sodium-ion battery is a Na-VPF system, with a charging voltage down to 4.3V and a discharging voltage down to 2.8V.

[0022] The sodium-ion battery high-voltage electrolyte and sodium-ion battery with matching sodium vanadium fluorophosphate cathode material proposed in this invention have the following beneficial technical effects:

[0023] (1) The sodium-ion battery high-voltage electrolyte and sodium-ion battery with matching sodium vanadium fluorophosphate cathode material proposed in this invention use high-concentration sodium salt electrolyte to match sodium vanadium fluorophosphate cathode material. Under high pressure, the decomposition of solvent at the interface is reduced and the amount of free solvent is reduced, thereby expanding the electrochemical window and greatly improving the cycle stability of sodium vanadium fluorophosphate cathode material.

[0024] (2) The sodium-ion battery high-voltage electrolyte and sodium-ion battery with matching sodium vanadium fluorophosphate cathode material proposed in this invention can still maintain a capacity retention rate of more than 90% after 80 cycles at high temperature and high pressure. After 280 cycles, the capacity retention rate can still reach 90.69%, which is far higher than that of conventional electrolytes in the prior art.

[0025] (3) The sodium-ion battery high-voltage electrolyte and sodium-ion battery with matching sodium vanadium fluorophosphate cathode material proposed in this invention not only have good high-voltage resistance, but also can form a more stable CEI film, avoiding the passivation ability of common non-high-voltage solvent differences. The high-concentration sodium salt electrolyte can enhance the interaction between cations and solvent molecules, reduce the reactivity of the solvent, reduce the occurrence of side reactions, inhibit the generation of HF, and improve the cycle performance of sodium vanadium fluorophosphate cathode material under high voltage.

[0026] (4) The sodium-ion battery high-voltage electrolyte and sodium-ion battery with matching sodium vanadium fluorophosphate cathode material proposed in this invention have better battery performance when using a concentration of 3.5 mol / L NaPF6. The capacity retention rate can reach 96.66% under high temperature and high pressure. This breaks the technical bias in the prior art that excessive sodium salt concentration leads to increased viscosity, difficulty in fully dissolving sodium salt, and easy deterioration of battery performance. Usually, the sodium salt concentration needs to be designed to not exceed 2 mol / L.

[0027] Additional aspects and advantages of the invention will be set forth in the description which follows, and in part will be obvious from the description or may be learned by practice of the invention. Attached Figure Description

[0028] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0029] Figure 1 The diagram shows the relationship between the number of cycles and the discharge specific capacity of sodium-ion batteries using the electrolyte prepared in Example 4 of the present invention and the electrolyte prepared in Comparative Example 2, after being left to stand at 60°C for 1 hour, 3 cycles at 0.1C, and then 280 cycles at 1C. Detailed Implementation

[0030] This invention discloses a high-voltage electrolyte and a sodium-ion battery that are compatible with sodium vanadium fluorophosphate cathode materials. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can obviously make modifications or appropriate alterations and combinations to the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.

[0031] The present invention will be further illustrated below with reference to the embodiments:

[0032] Example 1

[0033] The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and oxygen. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 3.0 mol / L NaPF6 was dissolved in the mixed solvent. The sodium salt and mixed solvent were then thoroughly mixed and allowed to stand for 6 hours before use.

[0034] Example 2

[0035] The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and oxygen. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 3.2 mol / L NaPF6 was dissolved in the mixed solvent. The sodium salt and mixed solvent were then thoroughly mixed and allowed to stand for 6 hours before use.

[0036] Example 3

[0037] The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and oxygen. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 3.4 mol / L NaPF6 was dissolved in the mixed solvent, and the sodium salt and mixed solvent were thoroughly mixed. The mixture was allowed to stand for 6 hours before use.

[0038] Example 4

[0039] The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and oxygen. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 3.5 mol / L NaPF6 was dissolved in the mixed solvent. The sodium salt and mixed solvent were then thoroughly mixed and allowed to stand for 6 hours before use.

[0040] Example 5

[0041] The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and oxygen. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 3.6 mol / L NaPF6 was dissolved in the mixed solvent. The sodium salt and mixed solvent were then thoroughly mixed and allowed to stand for 6 hours before use.

[0042] Example 6

[0043] The electrolyte was prepared in a glove box filled with argon gas, with a water content of less than 1 ppm and an oxygen content of less than 1 ppm. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 3.8 mol / L NaPF6 was dissolved in the mixed solvent, and the sodium salt and mixed solvent were thoroughly mixed. The mixture was allowed to stand for 6 hours before use.

[0044] Example 7

[0045] The electrolyte was prepared in a glove box filled with argon gas, with a water content of less than 1 ppm and an oxygen content of less than 1 ppm. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed evenly at a volume ratio of 3:7 to obtain a mixed solvent. 4 mol / L NaPF6 was dissolved in the mixed solvent. The sodium salt and the mixed solvent were thoroughly mixed and allowed to stand for 6 hours before use.

[0046] Comparative Example 1

[0047] The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and oxygen. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 0.8 mol / L NaPF6 was dissolved in the mixed solvent. The sodium salt and mixed solvent were then thoroughly mixed and allowed to stand for 6 hours before use.

[0048] Comparative Example 2

[0049] The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and oxygen. Sodium hexafluorophosphate was used as the sodium salt. Ethyl fluorocarbonate and ethyl methyl carbonate were mixed thoroughly at a volume ratio of 3:7 to obtain a mixed solvent. 1.0 mol / L NaPF6 was dissolved in the mixed solvent, and the sodium salt and mixed solvent were thoroughly mixed. The mixture was allowed to stand for 6 hours before use.

[0050] Preparation and testing of sodium-ion batteries

[0051] Preparation of the positive electrode sheet: Na3V2(PO4)2F3 powder, conductive carbon black, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1. The mixture was then thoroughly mixed with N-methylpyrrolidone (NMP) to form a slurry. This slurry was coated evenly onto aluminum foil and dried in an 80°C forced-air drying oven for 12 hours. After compaction using a tablet press, the slurry was cut into 14mm electrode sheets and vacuum dried at 80°C for 12 hours. The sheets were then weighed and placed in a glove box.

[0052] Battery assembly: Place the positive electrode in the middle of the negative electrode shell, then use a dropper to draw a small amount of electrolyte and drop 2-3 drops onto the electrode. Place the separator on top, then drop 3-4 more drops of electrolyte. Place the smoother side of the positive electrode on the battery, then place the foamed nickel and negative electrode shell on top. Finally, use a battery sealing machine to press the battery to 550 kPa to assemble it into a CR2025 battery. After standing for 10 hours, test it.

[0053] High-temperature and high-pressure cycle performance tests were conducted on sodium-ion batteries using the electrolytes in Examples 1 to 7 and Comparative Examples 1 and 2. Cycling parameters were set as follows: the battery was allowed to stand at 60°C for 1 hour, then cyclically charged at 0.1C for 3 cycles, followed by cyclically charged at 1C for 280 cycles. Constant current charge-discharge was used, with voltage limits of 2.8V-4.3V, meaning the charging voltage was capped at 4.3V and the discharging voltage at 2.8V. The test results are shown in Table 1 below. Figure 1 As shown.

[0054] Table 1. Results of High Temperature and High Pressure Cyclic Performance Test

[0055] Example 1 80 90.68% Example 2 80 92.18% Example 3 80 94.32% Example 4 80 96.66% Example 5 80 95.89% Example 6 80 95.32% Example 7 80 93.73% Comparative Example 1 80 70.56% Comparative Example 2 80 59.85%

[0056] Results Analysis

[0057] From Table 1 and Figure 1 As can be seen, the high-voltage electrolyte proposed in this invention retains over 90% of its capacity after 80 cycles of high-temperature and high-pressure cycling. In particular, in Example 4, the capacity retention rate reaches 96.66%, far exceeding the high-temperature and high-pressure capacity retention rate of conventional electrolytes in the prior art. At a high voltage of 4.3V, the reduced solvent decomposition at the interface leads to a decrease in the amount of free solvent, expanding the electrochemical window and significantly improving the cycle stability of the sodium vanadium fluorophosphate cathode material. This overcomes the technical bias in the prior art where excessively high sodium salt concentration leads to increased viscosity, difficulty in fully dissolving sodium salt, and a rapid deterioration of battery performance, typically requiring the sodium salt concentration to be designed to not exceed 2 mol / L.

[0058] The high-voltage electrolyte proposed in this invention exhibits superior battery performance at a NaPF6 concentration of 3.5 mol / L. (See Table 1 and...) Figure 1 As shown, using the high-voltage electrolyte in Example 4 of this invention, matched with sodium vanadium fluorophosphate, the capacity retention rate reached 96.66% after 280 cycles at 4.3V and 1C. Under the same conditions, using the conventional electrolyte in Comparative Example 2, the electrolyte failed after only 73 cycles.

[0059] The high-concentration sodium salt electrolyte proposed in this invention, matched with sodium vanadium fluorophosphate cathode material, can effectively improve the cycle stability of the battery. Moreover, the SEI film formed is more stable and less easily dissolved by solvents, reducing the self-decomposition phenomenon of electrolyte on the electrode material surface, and greatly increasing the application range of sodium-ion batteries.

[0060] The high-concentration sodium salt electrolyte and sodium vanadium fluorophosphate cathode material proposed in this invention not only have good high-voltage resistance, but also can form a better CEI film, avoid the passivation ability of common non-high-voltage solvent differences, enhance the interaction between cations and solvent molecules, reduce solvent reactivity, reduce side reactions, and inhibit HF generation, thereby improving the cycle performance of sodium vanadium fluorophosphate cathode material under high voltage.

[0061] The high-concentration sodium salt electrolyte proposed in this invention, matched with sodium vanadium fluorophosphate cathode material, increases the interaction between solvent molecules and anions and cations through the high-concentration electrolyte, and reduces the amount of free solvent in the electrolyte system, thereby weakening the dissolution effect of free solvent on SEI and achieving the effect of stabilizing the battery interface. Furthermore, under this high-concentration sodium salt, a new special three-dimensional electrolyte structure is formed, which can achieve significant advantages such as high rate performance, high cycle stability, high energy density, and high safety.

[0062] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A high-voltage electrolyte for sodium-ion batteries that is compatible with sodium vanadium fluorophosphate cathode material, characterized in that, include: The sodium salt and non-aqueous organic solvent are provided, wherein the sodium salt is one or more of sodium hexafluorophosphate, sodium bis(oxalato)borate, sodium difluorooxalatoborate, and sodium difluorosulfonamide, and the concentration of the sodium salt is 3.5 mol / L; and the non-aqueous organic solvent is a mixture of fluoroethylene carbonate and methyl ethyl carbonate in a volume ratio of 3:

7.

2. The sodium-ion battery high-voltage electrolyte according to claim 1, characterized in that, The sodium salt is sodium hexafluorophosphate.

3. The high-voltage electrolyte for sodium-ion batteries according to claim 2, which is matched with sodium vanadium fluorophosphate cathode material, is characterized in that, The electrolyte was prepared in a glove box filled with argon gas and containing less than 1 ppm of water and less than 1 ppm of oxygen. The water content of the non-aqueous organic solvent is less than 1 ppm; The water content of sodium salt is less than 1 ppm.

4. A sodium-ion battery, characterized in that, The sodium-ion battery high-voltage electrolyte used in any one of claims 1 to 3 is a positive electrode material of sodium vanadium fluorophosphate.

5. The sodium-ion battery according to claim 4, characterized in that, The mass ratio of positive electrode material, conductive agent, and binder in the positive electrode sheet is (7-9):(0.5-2):(0.5-1).

6. The sodium-ion battery according to claim 5, characterized in that, Sodium-ion batteries are Na-VPF systems, with a charging voltage cutoff of 4.3V and a discharging voltage cutoff of 2.8V.

Citation Information

Patent Citations

  • New electrolyte composition for sodium-ion battery

    CN112534618A

  • High-concentration aqueous electrolyte with wide electrochemical stability window and application thereof

    CN115377518A